An in-situ modification method for coal roadways with heightened burst risk - Ouyang, Zhenhua; Li, Gen; Wang, Qiong; Yi, Haiyang; Li, Zhengsheng; Shi, Qingwen (Frontiers in Earth Science, 2023)
In the coal mine with a heightened burst risk, the conventional support techniques are hard to achieve effective control of roadway and may cause burst fatalities. Thus, an in-situ modification method was proposed to improve the stability of burst roadway. The method artificially constructs a cracked zone and a reinforced zone by modifying the surrounding rock of roadway. Among the modified roadway, the cracked zone absorbs the dynamic energy generated by roof caving, and the reinforced zone stabilizes the surrounding rock of roadway. In this paper, the physical experiments were constructed to verify the efficiency of the in-situ modification method. Under the same engineering conditions, the reduction rates of dynamic stress at each part of modified roadway were greater than 82% compared with the unmodified roadway, which indicated the in-situ modification method has obvious effect on reducing coal burst rick. Subsequently, the in-fluence factors of the in-situ modification method were explored using numerical simulation. It was found that the thickness and the damage degree of cracked zone were key governing factors in reducing roadway dynamic energies and improving the roadway stabilities. Comparatively, the influences of reinforced zone thickness to the method were not obvious. The simulation results showed that the energy dissipation value increased as the thickness and the damage degree of cracked zone increase, but the energy dissipation rate became slower when the factors increased to a certain value. It also found that the regional variation differences of dynamic stress under different factor values. Exactly, the dynamic responses of roadway side were extremely sensitive to thickness and damage degree of cracked zone, even with the cracked zone thickness of 1 m and the damage degree of 30%. However, the dynamic responses of roadway top and roadway bottom exhibited a lower energy absorption capacity in conditions of smaller thickness and damage degree of cracked zone. This work provides an effective and economical method for coal roadways with heightened burst risk.